New Transcriptional Reporters to Quantify and Monitor PPARγ Activity - Séverine A. Degrelle; Hussein Shoaito; Thierry Fournier (PPAR Research)
The peroxisome-proliferator-activated-receptor-γ (PPARγ) is a member of the nuclear receptor superfamily that plays a critical role in diverse biological processes, including adipogenesis, lipid metabolism, and placental development. To study the activity of PPARγ, we constructed two new reporter genes: a fluorescent GFP-tagged histone-2B (PPRE-H2B-eGFP) and a secreted nanoluciferase (PPRE-pNL1.3[secNluc]). This study demonstrates their usage to monitor PPARγ activity in different cell types and screen for PPARγ’s potential ligands.